Léxico do discurso religioso: um estudo comparado - Danivia da Cunha Mattozo (2016)
This dissertation belongs to the domain of lexicological studies stemming from structural semantics. Its main sources are: Triers Lexical Field Theory (GEERAERTS, 2010); Matorés Social Lexicology (1973); and methodologically Sardinhas Corpus Linguistics (2004). Social reality has been shown to be an important ally of lexicon studies. Lexicon and reality go together, one being a reflection of the other. Religiousness is among the social aspects that pertain to the lexicon. Religious speakers have a specific lexicon, and the maintenance of such lexicon is directly related to the maintenance of their beliefs. The objective of this investigation was, therefore, to assess the religious lexicon of speakers from three different religions in order to verify by comparison if social differences expressed in doctrinal differences are, in fact, perceived in the lexicon. In order to do that, the social history and religious discourse of each church were researched. For social information, this investigation turned to the history, ecclesiastical organization, and doctrinal basis of each church. Lexical data came from online sermons by preachers of each church, following the principles of Corpus Linguistics, up to 250,000 words for each church, amounting to a corpus of 750,000 words. With the aid of a program called AntConc, a list of the 150 most frequent lexias in each church was created. The most frequent lemmata of each list were selected. Semantic networks and lexical fields were created from those lemmata with the aid of a program called CMapTools as a proposal for a description of the mental organization of the religious discourse lexicon. These data were analyzed and compared with the doctrinal basis in order to determine what the churches had in common and what was exclusive to each of them. After that, other descriptions of 13th, 15th, 16th and 20th-century religious lexicons were comparatively considered. The ensuing analysis confirmed the early hypothesis that speakers from different churches speak differently, since their lexicons mimic the doctrines of their respective churches. Thus, speakers speak differently concerning that which is doctrinally different and they speak alike concerning that which is doctrinally alike.